Basic cardiovascular physiology : from molecules to translational medical science - Pagliaro, Pasquale, 1961-; Penna, Claudia, 1967-; Rastaldo, Raffaella, 1970- (River Publishers, 2020)
This book focuses on established cardiovascular principles andhighlights some of the progress achieved by recent research in thecardiovascular field. The book describes the structure and function of theheart and vascular system for the reader to understand how the cardiovascularsystem responds in both health and disease.
Keywords: Cardiovascular system -- Physiology.; elektronické knihy; electronic books